122 ECAP-Controlled Closed-Loop Spinal Cord Stimulation (CL SCS): Double-Blind, Randomized Trial for the Treatment of Chronic Pain – 24-Month Outcomes. (1st April 2022) - Falowski, Steven M.
Abstract : INTRODUCTION: Evoked compound action potential (ECAP) recording provides an objective measure of spinal cord (SC) activation during SCS and can assist in programing of the SCS system. ECAP-controlled CL SCS, in which the stimulation output is automatically adjusted to maintain a desired ECAP amplitude, has been shown to provide effective pain relief in an open-label study (ACTRN12615000713594). METHODS: 134 subjects were enrolled and randomized after trial leads were implanted. The primary endpoint evaluated =50% reduction in overall back and leg pain measured by the Visual Analog Scale (VAS). Opioid usage and other patient-reported outcomes (PROs) including emotional/physical functioning, sleep quality, and quality of life were also collected. Additionally, objective neurophysiological data, including SC activation and time spent in the therapeutic range, were collected. RESULTS: Herein the Evoke Study Group reports the 24-month outcomes from this ongoing RCT. The proportion of implanted subjects with =50% overall back and leg pain reduction at 24 months was statistically superior in the CL vs. OL group (84.0% vs. 65.9% subjects, respectively; p = 0.040). Long-term improvements in all other PROs, including POMS, ODI, PSQI, EQ-5D-5L, and SF-12, were also demonstrated. Opioids were reduced or eliminated in 66.7% (CL) and 60.9% (OL), respectively. The most frequent level of SC activation was three times greater for CL (median ECAP Amplitude: 22.5 µV CL vs. 7.5 µV OL). SC activation was better maintained within the therapeutic range with CL (median: 93.9% CL vs. 46.1% OL). There were no differences in the safety profiles between treatment groups, and the type, nature, and severity of adverse events were similar to other SCS studies. CONCLUSION: In this ongoing study, ECAP-controlled CL SCS provided statistically superior pain relief and greater improvement in other PROs compared with OL SCS at 24 months. CL delivered greater levels of SC activation and better maintained SC activation in the subject's therapeutic range.